The Black Cauldron - Alexander, Lloyd. frey50 (New York : H. Holt, 1999)
Taran, Assistant Pig-Keeper of Prydain, faces even more dangers as he seeks the magical Black Cauldron, the chief implement of the evil powers of Arawn, lord of the Land of Death.
Keywords: Fantasy